The Predictive Value of the Clinical Frailty Scale on Discharge Destination and Complications in Older Hip Fracture Patients. Issue 10 (October 2019) - Chan, Sarah; Wong, Eric K. C.; Ward, Sarah E.; Kuan, David; Wong, Camilla L.
Abstract : Objectives: To determine whether the Clinical Frailty Scale (CFS), a validated frailty tool, was associated with discharge destination. Secondary objectives were to determine whether the CFS was associated with in-hospital complications and length of stay. Design: This is a 5-year retrospective cohort study. Setting: The study took place at an academic Level 1 trauma center. Patients/Participants: All patients 65 years of age and older admitted with an isolated hip fracture were included (N = 423). Intervention: Preadmission CFS was determined as part of routine clinical care prospectively and abstracted from the chart. Main Outcome Measurements: We collected demographic and process data associated with adverse outcomes (age, sex, time to surgery, and mode of anesthesia) and used multivariable logistic regression to determine the association between CFS with discharge destination, in-hospital complications, and length of stay. Results: Preadmission frailty was independently associated with adverse discharge destination (adjusted odds ratio 23.0; 95% confidence interval, 3.0–173.5) and in-hospital complications (adjusted odds ratio 4.8; 95% confidence interval, 2.1–10.8) in greater magnitude than traditional risk factors such as age, male sex, time to surgery, and mode of anesthesia. There was a dose–response relationship between increasing frailty and length of stay ( P < 0.001). Conclusions: Preadmission frailty as quantified by the CFS is associated with discharge destination, in-hospital complications, and length of stay. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.